Computational Investigations of Glare: Fatigue and Fracture Studies - Sunil Bhat; S. Narayanan (Computational Investigations of Glare: Fatigue and Fracture Studies, 2023)
The book presents detailed theoretical and numerical studies for investigation of the mechanisms of crack tip stress amplification, shielding and fiber bridging in two possible variants of Mode I cracked fiber metal laminate (Glare), Type I and Type II. The influence of residual stresses, that are generated due to curing during fabrication of the laminates, is incorporated in the study. Crack tip stress amplification is noticed in Type I whereas crack tip shielding is observed in Type II laminate. The effects are quantified with the help of theoretical and finite element models. The models are well substantiated by experiments.